AKAD HIBRID DALAM SURAT EDARAN BANK INDONESIA NOMOR 14/7/BPbS : ANALISIS HUKUM PADA PRODUK QARDH BERAGUN EMAS - Satria, Muhammad Hatta (Jurisdictie: Jurnal Hukum dan Syariah, 2016)
AbstractImplementation of the hybrid contract on qardh secured gold products consists of some contract, namely al-qardh, Rahn and Ijarah. This study focuses on the analysis of the hybrid contract on products qardh secured gold in Bank Indonesia Circular Letter No. 14/7 / BPbS. In this study the authors use research methods to examine normative juridical construction of the secured some financing agreement qardh gold. The results of the research, contract hybrids in product qardh secured gold to avoid the three problems, namely contract hybrids in buying, selling and borrowing, two sale and purchase agreement in the purchase contract, and two transactions in one transaction, for their firmness in the separation agreement between the contract tabarru 'with mu'Äwadhah contract. Hybrids contracts in product qardh gold secured in accordance with the pillars and the terms of the contract, as well as the condition of legitimacy, namely the submission that does not cause any harm, gharar (vagueness), the terms imperfect, and usury.Keyword: hybrid contract; Qardh secured goldÂ AbstrakImplementasi akad hibrid pada produk qardh beragun emas terdiri dari beberapa akad, yaitu al-qardh, rahn dan ijÄrah. Penelitian ini berfokus pada analisis akad hibrid pada produk qardh beragun emas dalam Surat Edaran Bank Indonesia Nomor 14/7/BPbS . Dalam penelitian ini penulis menggunakan metode penelitian normatif dengan mengkaji konstruksi yuridis beberapa akad pembiayaan qardh beragun emas. Hasil penelitian, akad hibrid pada produk qardh beragun emas terhindar dari tiga masalah, yaitu akad hibrid dalam jual beli dan pinjaman, dua akad jual beli dalam satu akad jual beli, dan dua transaksi dalam satu transaksi, karena adanya ketegasan dalam pemisahan akad antara akad tabarruâ€™ dengan akad muâ€™Äwadhah. Akad hibrid pada produk qardh beragun emas sesuai dengan rukun dan syarat akad, serta syarat keabsahannya, yaitu penyerahan yang tidak menimbulkan kerugian, gharar (ketidakjelasan), syarat-syarat fasid, dan riba.Keyword: akad hybrid; Qardh beragun emas